Pengaruh E-Commerce, Pengetahuan Kewirausahaan dan Sistem Informasi Akuntansi pada Minat Berwirausaha - Ellista Delvisa; Riswan (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
The purpose of this study is to analyze the impact of the use of e-commerce, business knowledge and accounting information systems on the entrepreneurial interests of students of the Accounting Studies Program at Bandar Lampung University. Research results show that there is a significant positive impact on students' interest in entrepreneurship between e-commerce, entrepreneurial knowledge, and the use of accounting information systems. This finding has important implications for the development of college student entrepreneurship. By improving their understanding and use of e-commerce, and good business skills, students are better prepared and motivated to develop their own businesses. A good understanding of accounting information systems also helps students manage their businesses effectively. Recommendations for educational institutions are to improve students' understanding and knowledge of e-commerce, entrepreneurship, and the use of accounting information systems through the development of relevant curricula. Governments and related parties can also support the development of e-commerce and create a favorable environment for the growth of student businesses. This research has made an important contribution to our understanding of the factors that influence students' interest in entrepreneurship and will serve as a reference for efforts to increase student entrepreneurship interest and promote entrepreneurial economic growth. can be used as.